The evolution of EUropean border governance through crisis: Frontex and the interplay of protracted and acute crisis narratives. (February 2023) - Perkowski, Nina; Stierl, Maurice; Burridge, Andrew
Crisis narratives are widespread in migration and border governance globally, including in EUrope. In response, a body of scholarship that critically scrutinizes crisis narratives and imaginaries has emerged. Building on and further extending this scholarship, this article questions the dichotomy between 'normality' and 'crisis' in border governance. Focusing on four moments in which crises were declared in relation to migration and EUropean borders and their immediate aftermath, we examine how the European Union border agency Frontex framed these events through an analysis of its press releases, annual reports, and practices. In so doing, we argue that narratives pertaining to border practices beyond moments of 'crisis' invoke fears of uncontrolled mass migration of unruly 'others' as an ever-present possibility and perpetual threat to EUrope. Within this article, we propose a differentiation between protracted and acute crisis narratives. Focusing on the political work that these two narratives do in relation to EUropean border governance, we demonstrate that the interplay between these crises narratives has contributed to Frontex's evolution and expansion over the last two decades while further consolidating the externalization and fortification of EUropean borders.